The Relationships between PsyCap, Academic Engagement and Academic Performance amongst Postgraduate Students in a South African Higher Education Institution - Veldsman, Nadine (Organisational Psychology, 2019)
In recent years, South African higher education institutions have consistently reported considerably low postgraduate throughput rates. It has thus become increasingly important to investigate what factors contribute to the academic success of postgraduate students. To this end, the researcher sought to examine the relationships between Psychological Capital (PsyCap) (the composite construct and its individual dimensions) academic engagement and academic performance. Age, gender and previous performance were included as covariates of academic performance. Moreover, she assessed whether PsyCap was a stronger predictor of academic engagement and performance than hope, self-efficacy, resilience and optimism respectively. Postgraduate students in a South African university participated in the self-report survey (N = 234). Exploratory factor analysis revealed that PsyCap and academic engagement were three-dimensional and two-dimensional constructs respectively. Pearson product-moment correlation showed that PsyCap, hope, self-efficacy and optimistic-resilience were positively related to academic engagement. PsyCap, its individual dimensions (barring optimisticresilience) and academic engagement additionally shared a positive relationship with academic performance. However, multiple regression analysis indicated that, when controlling for the covariates, only hope was a statistically significant psychological predictor of academic performance. Gender and previous academic performance were also consistently shown to uniquely predict academic performance. Suggestions for future research and the implications, theoretical as well as practical, are presented.